GAYA HIDUP BERKELANJUTAN SOSIALISASI DAN PRAKTEK DI RA TAUFIQURRAHMAN, BEJI TIMUR DEPOK - Nuringsih, Kartika; Edalmen,; Harry Kristanto, (Jurnal Bakti Masyarakat Indonesia, 2025)
This activity aims to introduce a sustainable lifestyle to children in Raudhatul Athfal (RA) Taufiqurrahman, Beji Timur Village, Depok. Along with climate change, it causes shifts in seasons so that during the dry season there is drought. On the other hand, during the rainy season it causes flooding or puddles. This situation has a negative impact on health, so it is time for people to adopt a sustainable lifestyle to play a role in maintaining economic, social and environmental sustainability. Conceptually, this lifestyle is a manifestation of the circular economic development model to accelerate the achievement of the SDGs by 2030. Socialization is needed as a mechanism to enrich knowledge and get used to a sustainable lifestyle. Socialization material related to (1) reduce, reuse and recycle, (2) plastic diet, (3) consumption of local vegetables and fruits, (4) saving clean water, and (5) reducing vehicle use by walking. The solution criteria are: Children are involved in activities so they understand examples of sustainable lifestyles. This is done through recycling activities for school crafts and eating local fruit/vegetables which are widely grown or sold around Depok City, such as: bananas, papaya, mangoes and others. As an evaluation, students' daily habits were selected, namely: (1) shopping habits, (2) consumption or eating patterns, and (3) transportation. The target of the activity is that children can know and practice this lifestyle so that when they continue to elementary school level, they have already received this knowledge.